2013
DOI: 10.1189/jlb.0113018
|View full text |Cite
|
Sign up to set email alerts
|

Decreased frequency of CD73+CD8+ T cells of HIV-infected patients correlates with immune activation and T cell exhaustion

Abstract: Recent studies indicate that murine Tregs highly express the ENTDP1, as well as the 5=-NT and thereby, suppress Teff function by extracellular adenosine production. Furthermore, CD73 seems to play a role as costimulatory molecule for T cell differentiation. In this study, we analyzed the expression of CD73 on peripheral and lymph nodal Teffs and Tregs in a cohort of 95 HIV patients at different stages of disease, including LTNP and ECs. In contrast to murine Tregs, CD73 was only expressed on a small minority (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 63 publications
(64 reference statements)
7
58
3
Order By: Relevance
“…These findings corroborate reports showing a strong correlation between downregulation of CD73 expression on CD8 ϩ T cells and high levels of immune activation in HIV-infected patients (48). Altogether, these seminal studies point to a previously unrecognized functional role of the ADO pathway in modulating HIV-1-associated immune activation.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These findings corroborate reports showing a strong correlation between downregulation of CD73 expression on CD8 ϩ T cells and high levels of immune activation in HIV-infected patients (48). Altogether, these seminal studies point to a previously unrecognized functional role of the ADO pathway in modulating HIV-1-associated immune activation.…”
Section: Discussionsupporting
confidence: 80%
“…While murine Tregs coexpress CD39 and CD73 (34,79), few human circulating CD4 ϩ T cells coexpress both ectoenzymes. Only one prior study (48) reported increased CD39/CD73 coexpression on T cells isolated from LNs from HIV patients. This prompted us to assess the frequency of the coexpression of these ADO production markers in order to more extensively characterize this pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). In humans, only a small fraction of Tregs express CD73 in steady-state ( 12 ). In response to IL2, however, the majority of human Tregs express both CD39 and CD73 ( 13 ).…”
Section: Adenosine-abundant Tumor Microenvironmentmentioning
confidence: 99%
“…Recently, a subset of these T follicular cells expressing FoxP3 has been described. This transcription factor defines T regulatory cells, a CD4 T-cell subset that limit effector T-cell response and maintain peripheral tolerance (Ramiscal and Vinuesa 2013) by modulating the dephosphorylation pathway of ATP (Toth 2013). Mice studies have shown that these T follicular regulatory (TFR) cells localize in the B-cell follicles and can regulate humoral immune responses through repressing TFH cells and GC formation.…”
Section: Cd4 T Follicular Cell Subsetsmentioning
confidence: 98%